KOMUNIKASI INTERPERSONAL ANTARA ROLEPLAYER DALAM MEMBANGUN SEBUAH HUBUNGAN PERTEMANAN PADA MEDIA SOSIAL TWITTER - Hendi Budi Wibowo; Christina Christina (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
One of the affected activities in social media that require users or individuals to carry out interpersonal interactions to interact with each other, one of these activities is Roleplaying. Roleplaying is a role-playing activity carried out on social media such as Facebook, Twitter, Telegram, and others. This roleplay activity is usually played by a group of film fans, K-Pop, and other cultures. This study aims to study the communication pattern used by Roleplayers and study how they build relationships with each other. The theory used in this research is dramaturgy theory, while the method used in this research is a qualitative method using the phenomenological tradition. Data collection methods were collected through observation, interviews, documentation, and literature study. The result of the study found that Roleplaying activities were carried out to socialize, fill spare time, and learn about new things together with new people who have the same hobby.